Understanding and prediction of Indian Northeast Monsoon over the years - Raj, Y. E. A .; Balachandran, S.; Amudha, B.; Geetha, B. (MAUSAM, 2025)
The five meteorological sub-divisions of India viz. Tamil Nadu, Coastal Andhra Pradesh, Rayalaseema, South Interior Karnataka and Kerala which together are referred here as the Southern Peninsular Region (SPR), are the major beneficiaries of Indian northeast monsoon which prevails over SPR during Oct-Dec. In this article how the knowledge base on Indian northeast monsoon evolved in the 19th, 20th and 21st centuries is presented. The article describes the transition from the southwest monsoon season to northeast monsoon season. The northeast monsoon rainfall (NMR) climatology of SPR based on 150 year data of 1871-2020 is presented and discussed. How the onset and withdrawal dates of northeast monsoon for 1871-2020 have been determined in various studies is set out. The inter-annual, intra-seasonal and diurnal variation features of NMR, components and weather systems of northeast monsoon are described. Short, medium range and seasonal forecasting of NMR, global teleconnections, relation between NMR and Indian southwest monsoon rainfall are elaborated. The climatic classification of SPR, research on northeast monsoon and a brief reference to the northeast monsoon of Sri Lanka are included.